2001
DOI: 10.1083/jcb.200107057
|View full text |Cite
|
Sign up to set email alerts
|

A novel, high conductance channel of mitochondria linked to apoptosis in mammalian cells and Bax expression in yeast

Abstract: During apoptosis, proapoptotic factors are released from mitochondria by as yet undefined mechanisms. Patch-clamping of mitochondria and proteoliposomes formed from mitochondrial outer membranes of mammalian (FL5.12) cells has uncovered a novel ion channel whose activity correlates with onset of apoptosis. The pore diameter inferred from the largest conductance state of this channel is ∼4 nm, sufficient to allow diffusion of cytochrome c and even larger proteins. The activity of the channel is affected by Bcl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
296
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 259 publications
(319 citation statements)
references
References 45 publications
(83 reference statements)
20
296
1
2
Order By: Relevance
“…Therefore the assumption is that release of apoptogenic factors from the IMS in this setting, must be controlled by another channel(s) [17]. Indeed, previous reports demonstrated the identification of the mitochondrial apoptosis induced channel (MAC) that has functional characteristics which are different from VDAC, and whose activity was detected in the VDAC-disrupted yeast strain [36][37][38][39].…”
Section: The Involvement Of Vdac In Apoptosismentioning
confidence: 99%
“…Therefore the assumption is that release of apoptogenic factors from the IMS in this setting, must be controlled by another channel(s) [17]. Indeed, previous reports demonstrated the identification of the mitochondrial apoptosis induced channel (MAC) that has functional characteristics which are different from VDAC, and whose activity was detected in the VDAC-disrupted yeast strain [36][37][38][39].…”
Section: The Involvement Of Vdac In Apoptosismentioning
confidence: 99%
“…34 This Bax-variant targets yeast mitochondria, is inserted in the outer membrane and is able to form a large cytochrome c-permeable channel, identical to that observed in apoptotic mammalian cells. 35 This simplified cellular system allows testing the effect of tBid on the function of Bax, independently of the apoptotic network. Following the expression of the proteins alone or in combination, mitochondria were isolated and the spectrophotometric measurement of the amount of mitochondrial cytochromes allows visualization of the release of cytochrome c, while the amounts of membrane-attached cytochromes b and aa 3 serve as internal controls (Figure 5a).…”
Section: Cl-dependent Synergetic Action Of Tbid and Bax On Cytochromementioning
confidence: 99%
“…34,35 High-level expression was carried Essential role of cardiolipin in tBid functions F Gonzalvez et al out with the GAL1/10 promoter as follows: HT444/Bax and SM400/Bax cells were grown aerobically in a complete medium YPL (1% yeast extract, 0.1% potassium phosphate, 0.12% ammonium sulfate, 2% lactate, pH 5.0) until the early-exponential growth phase. Galactose (1%) was added to induce Bax expression, cells were harvested after 90 min and mitochondria were isolated for cytochrome c measurement.…”
Section: Heterologous Expression Of Proapoptotic Proteins and Measurementioning
confidence: 99%
“…This channel has similar biophysical properties to those of VDAC, also called poreforming proteins, first found in outer mitochondrial membranes and later in cell membranes as well (Thinnes et al, 1989). In mitochondria, the VDACs are responsible for the movement of adenine nucleotides and there is some discussion as to their involvement in the initiation of apoptosis (Pavlov et al, 2001). Dermietzel et al (1994) identified a brain-derived pl-VDAC-1 channel in the cell membrane of astrocytes in situ.…”
Section: Porinsmentioning
confidence: 99%